Horizontal Depth : A New Database on the Content of Preferential Trade Agreements - Hofmann, Claudia; Osnago, Alberto; Ruta, Michele (World Bank, Washington, DC, 2017)
Preferential trade agreements are an important feature of the global trade system. Several questions, ranging from the rationale for preferential arrangements to their impact on members, non-members and the broader multilateral trade system, are at the forefront of academic and policy debates in trade policy. This paper contributes to the literature in two ways. First, it presents a new database that offers a detailed assessment of the content of preferential arrangements, examining the coverage and legal enforceability of provisions. The database covers 279 agreements signed by 189 countries between 1958 and 2015, which reflects the entire set of preferential trade agreements in force and notified to the World Trade Organization as of 2015. Second, the paper presents some novel stylized facts on preferential arrangements based on the analysis of the data. The key insight is that preferential trade agreements became deeper over time. A growing number of these treaties cover an extended set of policy areas, frequently with legally enforceable provisions, in areas under the current World Trade Organization mandate and in four leading areas outside the current World Trade Organization mandate: competition policy, investment, movements of capital, and intellectual property rights protection. Accounting for the changing coverage of preferential trade agreements, that is, their “horizontal depth,” is essential to gain a more complete and accurate understanding of where the global trading system is going and how its governance can be improved.